Patterns of medication errors involving pediatric population reported to the French Medication Error Guichet - Christine Azar; Delphine Allué; Marie B. Valnet-Rabier; Laurent Chouchana; Fanny Rocher; Dorothée Durand; Nathalie Grené-Lerouge; Nadine Saleh; Patrick Maison (Centro de Investigaciones y Publicaciones Farmaceuticas, 2021)
Background: Medication error is a global threat to patient safety, particularly in pediatrics. Yet, this issue remains understudied in this population, in both hospital and community settings. Objectives: To characterize medication errors involving pediatrics reported to the French Medication Error Guichet, and compare them with medication errors in adults, in each of the hospital and community settings. Methods: This was a retrospective secondary data analysis of medication errors reported throughout 2013-2017. Descriptive and multivariate analyses were performed to compare actual and potential medication error reports between pediatrics (aged <18 years) and adults (aged >18 and <60 years). Two subanalyses of actual medication errors with adverse drug reaction (ADR), and serious ADR were conducted. Results: We analyzed 4,718 medication error reports. In pediatrics, both in hospital (n=791) and community (n=1,541) settings, antibacterials for systemic use (n=121, 15.7%; n=157, 10.4%, respectively) and wrong dose error type (n=391, 49.6%; n=549, 35.7%, respectively) were frequently reported in medication errors. These characteristics were also significantly more likely to be associated with reported errors in pediatrics compared with adults. In the hospital setting, analgesics (adjusted odds ratio (aOR)=1.59; 95% confidence interval (CI) 1.03:2.45), and blood substitutes and perfusion solutions (aOR=3.74; 95%CI 2.24:6.25) were more likely to be associated with reported medication errors in pediatrics; the latter drug class (aOR=3.02; 95%CI 1.59:5.72) along with wrong technique (aOR=2.28; 95%CI 1.01:5.19) and wrong route (aOR=2.74; 95%CI 1.22:6.15) error types related more to reported medication errors with serious ADR in pediatrics. In the community setting, the most frequently reported pediatric medication errors involved vaccines (n=389, 25.7%). Psycholeptics (aOR=2.42; 95%CI 1.36:4.31) were more likely to be associated with reported medication errors with serious ADR in pediatrics. Wrong technique error type (aOR=2.71; 95%CI 1.47:5.00) related more to reported medication errors with ADR in pediatrics. Conclusions: We identified pediatric-specific medication error patterns in the hospital and community settings. Our findings inform focused error prevention measures, and pave the way for interventional research targeting the needs of this population.